A SEGREGAÇÃO URBANA EM PONTA GROSSA: O PROGRAMA BOLSA FAMILIA NO TERRITÓRIO DE ABRANGÊNCIA DO CRAS CARÁ-CARÁ - Havrechaki, Carlos Fabricio (2016)
This research’s purpose is to understand difficulties of families that reside in the area covered by CRAS Cará-Cará, in compliance with conditionalities before a segregated city. The urban formation process of Ponta Grossa, in relation to housing, was extremely segregating. In this consolidated urban segregation scenario, it is noticeable that direct income transfer policies, specifically Bolsa Família program (PBF), require the fulfillment of several conditionalities in order for assisted families to remain receiving the benefit. These requisites are directly connected to an egalitarian urban development, as they depend, basically, on the existence of elementary schools, day care centers and public medical facilities within the area in which beneficiaries inhabit. As these peripheries are, generally, outdated in relation to urban equipment, fulfillment of such conditionalities end up becoming one more difficulty in these individual’s lives, who mostly live in either poverty, or extreme poverty. We have analyzed the situation of 132 families that reside in the area covered by CRAS Cará-Cará, which is responsible for 37 neighborhoods, and covers part of the southern region of the city. In these families, there was 169 school age teenagers, between March 2013 and May 2015, in violation of conditionalities, all for school dropout, or truancy. Therefore, the research shows that the absence of schools and day care centers in these families’ neighborhoods, plus high school vacancies available only in night time, are the main causes of school dropouts, hence the violation of PBF’s conditionalities.